Advanced nanomaterials in agriculture under a changing climate: The way to the future? - Ioannou, Andreas; Gohari, Gholamreza; Papaphilippou, Petri Ch.; Panahirad, Sima; Akbari, Ali; Dadpour, Mohammad Reza; Krasia-Christoforou, Theodora; Fotopoulos, Vasileios (My University, 2020)
© 2020 Elsevier B.V. Global agricultural production is suffering substantial losses due to climate change-related phenomena such as drought and salinity, which lead to tissue damage and, ultimate, major yield losses. The development of sustainable, ‘green’ technologies is therefore becoming increasingly important. Nanotechnology provides invaluable tools to a variety of industrial sectors. Recent focus has been given to the development and optimization of nanomaterials for application in the agricultural industry towards improved growth, plant protection and overall performance based on their small size, high surface to volume ratio and unique optical properties. The present review provides an up-to-date description of advanced nanoparticles and polymers applied at plant and seed level, covering technical, biological and socioeconomical aspects of this promising approach. This technology offers an attractive alternative to established approaches such as conventional breeding and genetic modification with key advantages, representing a characteristic example of integrative plant physiology where multiple disciplines such as materials science, agriculture and analytical chemistry join forces to develop exciting new tools in modern agriculture.
Keywords: Abiotic stress; Biotechnology; Nanomaterials; Nanoparticles; Priming; Seed coatings